Tuning lattice strain in biphenylene for enhanced electrocatalytic oxygen reduction reaction in proton exchange membrane fuel cells. (15th October 2022) - Feng, Zhen; Fang, Miaomiao; Li, Renyi; Ma, Bingxin; Wang, Huimin; Ding, Hai; Su, Guang; Tao, Kai; Tang, Yanan; Dai, Xianqi
Abstract: As proton-exchange membrane fuel cell technology has grown and developed, there has been increasing demand for the design of novel catalyst architectures to achieve high power density and realize wide commercialization. Herein, based on the two-dimensional biphenylene, we compare the oxygen reduction reaction (ORR) activity on the active sites with different biaxial lattice strains using first-principles calculations. The ORR free energy diagrams of biphenylene monolayers with varying lattice strains suggest that the biaxial tensile strains are unfavorable for catalytic activity. In contrast, the biaxial compressive strains could improve the catalytic performance. The biphenylene systems with the strain of −2% ∼ −6% ( S -0.02∼-0.06 ) display overpotentials of 0.37–0.49 V. This performance is comparable to or better than the Pt (111) surface. The Bader charge transfer of adsorbed O species on various biaxial strain biphenylene catalysts could be a describer to examine the catalytic activity. The catalysts possessed the moderate transferred charge of O adsorbed species often promotes catalytic process and give the high catalysis efficiency. Overall, this work suggests that the lattice strain strategy can significantly enhance the catalytic activity of biphenylene materials and further provide guidance to design biphenylene-based catalysts in various chemical reactions. Graphical abstract: Image 1 Highlights: Lattice strains in 2D biphenylene could enhance ORR activity. Compressive strains of −2% ∼ −6% endow their overpotentials of 0.37–0.49 V. Charge transfer of adsorbed O species is a descriptor to examine ORR performance. Moderate strains and moderate transferred charge lead to excellent efficiency.